Nakłady na ochronę roślin na obszarach górskich na przykładzie powiatu kłodzkiego - Golinowska, Maria (The Outlays on Plant Protection in Mountain Areas on the Example of Kłodzko District, 2005)
In 2002 in the Kłodzko district situated in the area of the Sudety Mountains the research was carried out which aim was to determine the level of outlays on plant protection on farms equipped with spraying machines, as well as the analysis of the Code of Good Practice in Plant Protection. The research shows that the agricultural producers in the Kłodzko district in the Sudety have serious problems with conforming to the Code of Good Practice in Plant Protection, connected with the technology of using pesticides, such as: storing the means of plant protection, dealing with the water left after the treatments, utilising the packages and keeping the equipment in working order.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 249-255